Fire-Resistant Geopolymers - Vickers, L.; Van Riessen, Arie; Rickard, W. (Springer, 2014)
The book covers the topic of geopolymers, in particular it highlights the relationship between structural differences as a result of variations during the geopolymer synthesis and its physical and chemical properties.